A follow-up study of the long-term satisfaction, reproductive experiences, and self-reported health status of oocyte donors in Spain. (4th May 2019) - Gonzalo, J.; Perul, M.; Corral, M.; Caballero, M.; Conti, C.; García, D.; Vassena, R.; Rodríguez, A.
Abstract: Purpose: The aim of this study is to evaluate the health of oocyte donors and explain how they regard their experience in the long-term. Materials and methods: This is a cross-sectional study in a single fertility centre that consists of a telephone interview guided by a semi-structured questionnaire covering several aspects of reproductive health and personal experience. Results: At the time of interview, 84 out of 121 women (69%) had children while 64 (53%) were already mothers at the time of their donation. Of the 38 women achieving a pregnancy after donation, five reported six pregnancy complications. Two out of 121 (2%) women reported being in menopause (aged 41 and 45). Twenty-three women (19%) reported gynaecological issues and eight (7%) reported fertility problems, although only four consulted a specialist. Most of women highlighted positive feelings about their donation (113, 93%) and 155 (97%) would recommend donating. Less than half (53, 44%) mentioned some negative aspects, mainly related to physical discomfort: injections (20, 17%), pain (17, 14%), and side effects of ovarian stimulation (10, 8%). Conclusion: The impact of donation on women's life was mostly favourable, with the majority of participants reporting positive aspects and recommending donation, although some negative feelings as physical discomfort also arose. Therefore, more comfortable stimulation protocols could be developed.